Meta-analysis of yield-emission trade-off in direct seeded vs. puddled transplanted rice: Towards a cleaner and sustainable production - Reddy, K. Srikanth; Parihar, C.M.; Panneerselvam, P.; Sarkar, Ayan; Patra, Kiranmoy; Bharadwaj, Sneha; Sena, D.R.; Reddy, G. Sreeja; Sinha, Alok; Dhakar, Rajkumar; Kumar, Virender; Nayak, Hari Sankar (Elsevier, 2025)
Conventional rice production through puddled transplanted rice-PTR is tillage, water, energy, and capital intensive. Furthermore, it is a major contributor to greenhouse gas (GHGs) emissions. In this regard, Direct seeded rice-DSR can be a potential alternative to PTR for reducing GHGs emissions, while sustaining yields. However, depending upon agroclimatic situation, whether the effect of DSR on GHGs emission and yield are consistent or not, as compared to PTR need a comprehensive analysis. To bridge this knowledge gap, we performed a meta-analysis synthesizing 876 paired measurements from 54-peer-reviewed studies to understand how DSR impacts N2O and CH4 emissions, global warming potential-GWP (heat-trapping potential of greenhouse gases compared to CO2), yield and C-footprint-CFP (environmental impact in CO2 eq. due to concerned activity). Compared to PTR, DSR decreased CH4 emissions by 70%, GWP by 37% and CFP by 34%, despite 85% increase in N2O emissions. However, this shift comes with 11% decrease in yield. To decipher the primary factors driving these outcomes, we conducted subgroup analyses by taking environmental conditions and management practices as predictors in a random effect model. Low to medium pH soils, zero tillage, puddled soil (wet DSR), conventional flooding, and high nitrogen rates (>200 kg/ha) are found to be favorable for DSR with comparable yields but posing a discrepancy with environmental sustainability benefits. Therefore, further research to evaluate DSR across agro-ecologies, management practices are needed to optimize yields with lower GWP and CFP.